The Development of the Ten-Year English Textbook Series for Vietnamese Schools under the National Foreign Language 2020 Project: A Cross-Cultural Collaborative Experience - Vân, Hoàng Văn (VNU Journal of Foreign Studies; Vol 31 No 3, 2015)
This paper attempts to give an account of the cross-cultural collaborative project between Vietnamese textbook writers and those of MacMillan Education and Pearson Education – two leading international second/foreign language textbook publishers – in producing the ten-year English textbook series for Vietnamese schools under the National Foreign Language 2020 Project. The paper is organized around three parts. Part one provides backgrounds to and bases for developing the textbook series. Part two describes in some detail the cross-cultural textbook development process the Vietnamese textbook writers and their collaborative colleagues of MacMillan Education and Pearson Education have been undertaking in developing the textbook series. Part three gives a résumé of what has been discussed, points out the advantages of the cross-cultural collaboration in producing the textbook series, and argues for a close collaboration between local textbook writers and writers who speak English as their mother tongue in producing high quality English textbooks that are suited to the general educational system of Vietnam. Keywords : Cross-cultural collaborative experience, textbook development, 2020 Project, three pilot English curricula, VNFLPF, CEFR, 20-step workflow.